2015
DOI: 10.1016/j.physleta.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Ship-induced solitary Riemann waves of depression in Venice Lagoon

Abstract: We demonstrate that ships of moderate size, sailing at low depth Froude numbers (0.37-0.5) in a navigation channel surrounded by shallow banks, produce depressions with depths up to 2.5 m. These depressions (Bernoulli wakes) propagate as long-living strongly nonlinear solitary Riemann waves of depression substantial distances into Venice Lagoon. They gradually become strongly asymmetric with the rear of the depression becoming extremely steep, similar to a bore. As they are dynamically similar, air pressure fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 31 publications
(41 reference statements)
1
51
0
Order By: Relevance
“…Bridges & Leeder, ; Choi et al ., , ). Although boat traffic in the Venice Lagoon could contribute to destabilizing the bar brink zone (Parnell et al., ; Rapaglia et al., ), the occurrence of detachment surfaces in bar deposits dates back to a few centuries ago (i.e. before the onset of boat traffic), thus suggesting that these processes commonly occur in natural systems and are not triggered by human influence.…”
Section: Discussionmentioning
confidence: 99%
“…Bridges & Leeder, ; Choi et al ., , ). Although boat traffic in the Venice Lagoon could contribute to destabilizing the bar brink zone (Parnell et al., ; Rapaglia et al., ), the occurrence of detachment surfaces in bar deposits dates back to a few centuries ago (i.e. before the onset of boat traffic), thus suggesting that these processes commonly occur in natural systems and are not triggered by human influence.…”
Section: Discussionmentioning
confidence: 99%
“…Virtually all records showed the development of a step on the rear slope of the depression wave. Parnell et al (2015) show that these waves are described reasonably well as long-living strongly nonlinear solitary Riemann depression waves. At those sites where water speeds were also recorded (B1, B2, W1 and W2), even small depression waves generated high near bed speeds (greater than 0.65 m/s in the examples shown).…”
Section: Resultsmentioning
confidence: 79%
“…The potential impact of depression waves propagating as strongly nonlinear Riemann waves across wide and shallow shoals has been demonstrated by Parnell et al (2015) and Rodin et al (2015). Provided that their amplitude is large enough to ensure a strongly nonlinear regime of propagation, waves generated in a narrow channel constructed in a shallow lagoon may penetrate to substantial distances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas like lagoons, which are protected from sea waves and winds, their effects are much more important than in the open sea. Several studies conducted in the Venetian Lagoon have shown that ships, especially large ones create significant depression waves (Rapaglia et al, 2011(Rapaglia et al, , 2015Parnell et al, 2015;Rodin et al, 2015;Gelinas et al, 2013). They can reach up to 2.5 metres in vertical displacement and can propagate up to 500 metres away from canals to shallow areas (Parnell et al, 2015).…”
Section: Waves and Vibrationsmentioning
confidence: 99%